(untitled) (Journal of Economic Research & Business Administration, 2018)
The article presents the results of theoretical review and materials generalization on the interpretation of human capital essence and it’s role. It is the main strategic resource capable of solving complex problems of the country’s transition to a «green economy». Human capital is considered by us as a set of certain personal, social, professional, business qualities, and is an important investment resource, the use of which contributes to the improvement of production efficiency. Considerable attention is paid to methodological aspects of human capital research. Despite the importance of productive use problem of human capital, the interrelationship of quality, personnel motivation and efficiency of its use is insufficiently researched, which caused the need for a more detailed research of this issue with the use of selective, monographic studies, statistical methods of researching stochastic connections. The research includes the following stages: analysis and assessment the level of human capital development in Kazakhstan against the background of developed foreign countries, identificate the factors affecting the use of this capital and the calculation of their relationship strength; formation of proposals for the accumulation, effective use and further human capital development in the agricultural sector.